2020
DOI: 10.1101/2020.06.23.166462
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The crystal structure of the Ca2+-ATPase 1 fromListeria monocytogenesreveals a pump primed for dephosphorylation

Abstract: Bacteria regulate intracellular calcium concentrations by exporting calcium from the cell using active transporters. These transporters include homologues of the mammalian sarco/endoplasmic reticulum Ca 2+ -ATPase (SERCA), which has served as a paradigm for the structure and mechanism of P-type ATPase ion transport. Here we present three crystal structures of the Ca 2+ -ATPase 1 from Listeria monocytogenes (LMCA1). Structures with BeF3mimicking a phosphoenzyme state reveal an intermediate between the outward-o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Notably, analogous highly similar BeF3 --and AlF4-stablized structures have recently also been observed for the Ca 2+ -specific P-type ATPase from Listeria monocytogenes (LMCA1) (43) . It was proposed that LMCA1 pre-organizes for dephosphorylation already in a late E2P state (E2P*, stabilized by BeF3 -), in accordance with its rapid dephosphorylation.…”
Section: Structures In Transition States Of Dephosphorylationmentioning
confidence: 57%
“…Notably, analogous highly similar BeF3 --and AlF4-stablized structures have recently also been observed for the Ca 2+ -specific P-type ATPase from Listeria monocytogenes (LMCA1) (43) . It was proposed that LMCA1 pre-organizes for dephosphorylation already in a late E2P state (E2P*, stabilized by BeF3 -), in accordance with its rapid dephosphorylation.…”
Section: Structures In Transition States Of Dephosphorylationmentioning
confidence: 57%
“…Surprisingly however, analysis of the two obtained structures suggests that the anticipated significant domain reorientations are absent in sCoaT (Figure 2b Notably, analogous highly similar BeF 3 --and AlF 4 -stablized structures have recently also been observed for the Ca 2+ -specific P-type ATPase from Listeria monocytogenes (LMCA1) (46) . It was proposed that LMCA1 pre-organizes for dephosphorylation Conversely, the M-domains of the two sCoaT structures are overall similar and appear outward-occluded (Figure 2c), as also supported by comparisons with the equivalent structures of SsZntA, again contrasting to the situation observed in P IB-1 -and P IB-2 -ATPases.…”
Section: Structures In a Transition State Of Dephosphorylationmentioning
confidence: 65%
“…Within the P2A subfamily members adapt to their specific environment. This is true for LMCA1 which has evolved to be a simple version of SERCA with fast dephosphorylation, reduced ion capacity and no dedicated proton pathways (38,42). Recently, structures of the secretory pathway Ca 2+ /Mn 2+ -ATPase (SPCA1) suggested that flexibility of TM2 and TM6 allows Ca 2+ and Mn 2+ to share the same binding site (43).…”
Section: Figure 3: P1b Heavy Metal Pumps P-type Atpase Colored As In ...mentioning
confidence: 99%